Prevalence of Obsessive Compulsive Symptoms in Medical and Dental Practitioners with Respect to Gender : Obsessive Compulsive Symptoms in Medical and Dental Practitioners - Ashraf, Aysham; Hassan, Syeda Alizeh; Butt, Hira; Anjum, Muhammad Suleiman; Babary, Darab Fatima; Khan, Nauman Rauf (Pakistan Journal of Health Sciences, 2023)
Obsessive compulsive disorder (OCD) comprises of mental images that provoke anxiety and fear and are recurrent. Objective: To find the prevalence of OCD symptoms in medical doctors and dentists with respect to gender. Methods: The study design was cross sectional comparative. It was conducted in College of Dentistry, Sharif Medical and Dental College Lahore. All practitioners irrespective of their age and gender were included in the study. Individuals practiced in a clinic or hospital for less than 6 months were excluded from the study. Obsessive compulsive inventory scale was used for data collection. Results: Gender of medical doctors and dentists and the symptom of washing (p=0.335, p=0.760 respectively), obsessing (p=0.131, p=0.476 respectively), checking (p=0.620, p=1.000 respectively) and neutralizing (p=0.294, p=1.000 respectively) was not significantly associated. The association between the symptom of ordering and gender of medical practitioners (p=0.05) was statistically significant. The association between gender of dental practitioners with hoarding (p=0.188), ordering (p=0.713) and doubting (p=1.000) was non-significant. Conclusions: Among the medical practitioners the symptoms of washing, obsessing, checking and neutralizing were higher in males as compared to the females. Among the dental practitioners the symptom of washing, obsessing and neutralizing were more prevalent in males while the symptom of checking was more prevalent in females. The symptoms of hoarding, ordering and doubting were more prevalent in males in comparison to female medical practitioners. Among the dental practitioners where the prevalence of hoarding was higher in the males while that of ordering and doubting was higher in the females.